Factors associated with enrolment into a national COVID-19 pulse oximetry remote monitoring programme in England: a retrospective observational study. Issue 4 (April 2023) - Clarke, Jonathan; Beaney, Thomas; Alboksmaty, Ahmed; Flott, Kelsey; Ashrafian, Hutan; Fowler, Aidan; Benger, Jonathan R; Aylin, Paul; Elkin, Sarah; Neves, Ana Luisa; Darzi, Ara
Summary: Background: Hypoxaemia is an important predictor of severity in individuals with COVID-19 and can present without symptoms. The COVID Oximetry @home (CO@h) programme was implemented across England in November, 2020, providing pulse oximeters to higher-risk people with COVID-19 to enable early detection of deterioration and the need for escalation of care. We aimed to describe the clinical and demographic characteristics of individuals enrolled onto the programme and to assess whether there were any inequalities in enrolment. Methods: This retrospective observational study was based on data from a cohort of people resident in England recorded as having a positive COVID-19 test between Oct 1, 2020, and May 3, 2021. The proportion of participants enrolled onto the CO@h programmes in the 7 days before and 28 days after a positive COVID-19 test was calculated for each clinical commissioning group (CCG) in England. Two-level hierarchical multivariable logistic regression with random intercepts for each CCG was run to identify factors predictive of being enrolled onto the CO@h programme. Findings: CO@h programme sites were reported by NHS England as becoming operational between Nov 21 and Dec 31, 2020. 1 227 405 people resident in 72 CCGs had a positive COVID-19 test between the date of programme implementation and May 3, 2021, of whom 19 932 (1·6%) were enrolled onto the CO@h programme. Of those enrolled, 14 441 (72·5%) were aged 50 years or older or were identified as clinically extremely vulnerable (ie, having a high-risk medical condition). Higher odds of enrolment onto the CO@h programme were found in older individuals (adjusted odds ratio 2·21 [95% CI 2·19–2·23], p<0·001, for those aged 50–64 years; 3·48 [3·33–3·63], p<0·001, for those aged 65–79 years; and 2·50 [2·34–2·68], p<0·001, for those aged ≥80 years), in individuals of non-White ethnicity (1·35 [1·28–1·43], p<0·001, for Asian individuals; 1·13 [1·04–1·22], p=0·005, for Black individuals; and 1·17 [1·03–1·32], p=0·015, for those of mixed ethnicity), in those who were overweight (1·31 [1·26–1·37], p<0·001) or obese (1·69 [1·63–1·77], p<0·001), or in those identified as clinically extremely vulnerable (1·58 [1·51–1·65], p<0·001), and lower odds were reported in those from the least socioeconomically deprived areas compared with those from the most socioeconomically deprived areas (0·75 [0·69–0·81]; p<0·001). Interpretation: Nationally, uptake of the CO@h programme was low, with clinical judgment used to determine eligibility. Preferential enrolment onto the pulse oximetry monitoring programme was observed in people known to be at the highest risk of developing severe COVID-19. Funding: NHS England, National Institute for Health Research, and The Wellcome Trust.